Ninth Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations. (Policy Papers; Policy Paper ;, 2018)
The Ninth Periodic Monitoring Report (PMR) on the Status of Management Implementation Plans (MIPs) in Response to Board-Endorsed Independent Evaluation Office (IEO) Recommendations assesses the progress made over the last year on actions contained in two 'new' MIPs arising from recent IEO evaluations, and another seven for which individual management actions were classified as 'open' in the Eighth PMR. Overall, 42 of the 96 actions included in the Ninth PMR remain open, representing roughly the same proportion as the previous PMR. A 25 percent net increase in open management actions over the past year is accounted for by 24 new actions from two MIPs, and 16 actions that have been implemented over the period. There is positive traction on the last four MIPs, but older actions appear challenging to implement. Better progress has been made with the implementation of the actions contained in recent MIPs. Fourteen of the actions implemented since the Eighth PMR relate to MIPs approved after October 2015, while only two actions (out of 24) from earlier MIPs were implemented. Improvements in the follow-up process approved by the Board in October 2015 have contributed to speedier implementation of recent actions, but some challenges remain. There are lingering challenges with defining measures of success for numerous actions, but accountabilities are now clearer and many actions are at advanced stages at the time of the Board's discussion of the MIPs. This PMR introduces indicators to support the process for resolving challenges with long-standing actions. Despite the slower progress with the older actions, significant advances have been made over the past year in several key areas. These include: protocols for engaging the IEO; risk management and analysis; the mainstreaming of macrofinancial surveillance; an overarching strategy on data and statistics; guidance on cooperation with other organizations, including Regional Financing Arrangements (RFAs); improvements in External Stability Assessments; and ongoing analytical work on surveillance and program, including macrostructural issues, emerging topics, and debt sustainability analysis. On the other hand, progress has been slower on macro forecasting, outward spillovers, and cross-country knowledge sharing.